IMPACT OF FORENSIC ACCOUNTING ON FRAUD DETECTION IN NIGERIAN DEPOSIT MONEY BANKS - Garba , Adamu (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
This study investigated the impact of forensic accounting on fraud detection in deposit money banks within Benue State, Nigeria, utilizing a cross-sectional research design. The population consisted of 145 employees from three deposit money banks operating in Makurdi Metropolis, Benue State. A census sampling technique was employed, and data were collected using a structured questionnaire validated through content and construct validity methods, achieving a Cronbach's Alpha reliability coefficient of 0.872. The study employed binary logistic regression to estimate the impact of forensic accounting variables on fraud detection. The findings reveal that Engagement of Forensic Accountants (EFA) significantly enhances fraud detection, with a coefficient (B) of 1.671 (SE = 0.414), Wald statistic of 9.830 (p 0.001), and odds ratio (Exp(B)) of 3.911. This implies a 291.1 increase in the likelihood of fraud detection with the engagement of forensic accountants, underscoring their pivotal role in improving financial transparency and accountability. Conversely, Litigation Support Skills (LSA) did not show a statistically significant impact on fraud detection (B = 0.541, SE = 0.378, p = 0.152), suggesting limited effectiveness in this context. However, Forensic Investigative Professional Skills (FIS) demonstrated a significant positive impact (B = 1.203, SE = 0.406, p = 0.015), increasing the likelihood of detecting fraud by 104.4. The study recommends that banks prioritize the integration of forensic accountants into internal audit processes to bolster fraud detection capabilities effectively. Furthermore, continuous professional development in forensic investigative techniques should be emphasized to enhance staff skills and readiness in identifying and mitigating complex fraud schemes.